Epidemiological Survey on the Perception of Adverse Effects in Women Using Contraceptive Methods in Brazil - Pannain, Gabriel Duque; Brum, Vivian de Oliveira Rodrigues; Abreu, Maria Mariana Andrade; Lima, Gabriela Barbosa (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2022)
Objective The present study aimed to understand patient perception of the adverse effects of contraceptives to improve health care and adherence to treatment.Methods An online questionnaire was available for women in Brazil to respond to assess their perception of adverse effects and their relationship with contraceptive methods.Results Of all 536 women who responded, 346 (64.6%) reported current contraceptive use. One hundred and twenty-two (122–34.8%) women reported having already stopped using contraception because of the adverse effects. As for the contraceptive method used, the most frequent was the combined oral contraceptive (212–39.6%). When we calculated the relative risk for headache, there was a relative risk of 2.1282 (1.3425–3.3739; 95% CI), suggesting that the use of pills increases the risk of headache, as well as edema, in which a relative risk of 1.4435 (1.0177–2.0474; 95% CI) was observed. For low libido, the use of oral hormonal contraceptives was also shown to be a risk factor since its relative risk was 1.8805 (1.3527–2.6142; 95% CI). As for acne, the use of hormonal contraceptives proved to be a protective factor, with a relative risk of 0.3015 (0.1789–0.5082; 95% CI).Conclusion The choice of a contraceptive method must always be individualized, and the patients must be equal participants in the process knowing the expected benefits and harms of each method and hormone, when present.
Keywords: contraception; hormonal contraception; drug-related side effects and adverse reactions; gynecology; epidemiology